2021
DOI: 10.1002/ange.202113340
|View full text |Cite
|
Sign up to set email alerts
|

Rhenium‐Mediated Conversion of Dinitrogen and Nitric Oxide to Nitrous Oxide

Abstract: Reductive splitting of N 2 is an attractive strategy towards nitrogen fixation beyond ammonia at ambient conditions. However, the resulting nitride complexes often suffer from thermodynamic overstabilization hampering functionalization. Furthermore, oxidative nitrogen atom transfer of N 2 derived nitrides remains unknown. We here report a Re IV pincer platform that mediates N 2 splitting upon chemical reduction or electrolysis with unprecedented yield. The N 2 derived Re V nitrides undergo facile nitrogen atom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Spectroscopic and crystallographic characterization of 1 b / c support rhenium(III) in meridional octahedral coordination [15] . As a typical trend for the halide precursors, [13e, 16] cyclic voltammetry (CV) showed that the first reduction of 1 b ( E 1/2 =−1.70 V vs. FeCp 2 +/0 ) [17] and 1 c ( E 1/2 =−1.52 V) are at significantly less negative potentials with respect to 1 a ( E 1/2 =−1.84 V) [18] . At lower scan rate, the Re III/II couple becomes irreversible for all three halides, which is attributed to X − loss from [ReX 3 ( H PNP)] − as a prerequisite to N 2 activation.…”
Section: Resultsmentioning
confidence: 97%
“…Spectroscopic and crystallographic characterization of 1 b / c support rhenium(III) in meridional octahedral coordination [15] . As a typical trend for the halide precursors, [13e, 16] cyclic voltammetry (CV) showed that the first reduction of 1 b ( E 1/2 =−1.70 V vs. FeCp 2 +/0 ) [17] and 1 c ( E 1/2 =−1.52 V) are at significantly less negative potentials with respect to 1 a ( E 1/2 =−1.84 V) [18] . At lower scan rate, the Re III/II couple becomes irreversible for all three halides, which is attributed to X − loss from [ReX 3 ( H PNP)] − as a prerequisite to N 2 activation.…”
Section: Resultsmentioning
confidence: 97%
“…A pincer ligand system by Schneider and coworkers has proven successful in dinitrogen activation using multiple strategies with different transition metal ions [13b,34b–c,39,49] . Redox potentials were calculated using the method described by Schneider and coworkers [39] .…”
Section: Methodsmentioning
confidence: 99%
“…4 Very recently, Schneider reported the first example of N-N coupling after N 2 splitting to form nitrous oxide. 5 In sharp contrast, studies on N-P bond formation are exceptionally scarce. Few examples have been reported over the past few decades, most of which, are intramolecular rearrangements of the phosphine ligand in the side-on N 2 -bridged Ti 6 or U 7 complexes.…”
mentioning
confidence: 99%